Variation of clinically relevant anatomical structures in general surgery : examples, analysis of related surgical complications and assessing the level of anatomical knowledge among practicing surgeons - Kowalczyk, Katarzyna Anna (2023)
Basic anatomical knowledge seems to be common for each diagnostic and therapeutic process. Surgery is a field of medicine for which knowledge of anatomy is crucial, and even without it, it does not exist. Every surgical procedure is connected with anatomic structures. A low level of anatomical knowledge can inevitably lead to surgical errors, and hence an understandable lack of achievement on the part of the ingredients, resulting in an increase in forensic ingredients. The lack of recognition of anatomical variations is often cited in the literature as a cause of surgical errors made even by experienced surgeons. Appropriate interventions should be provided to fill this potential gap in the anatomical knowledge of clinicians. Such preventive interventions help in surgical treatment, minimizing the use of reoperation and improve patient satisfaction by avoiding unwanted medical errors. The level of anatomical knowledge of Polish surgeons is essential. It may be beneficial to provide surgeons with access to cadaver courses during specialization training which is the most effective form of learning anatomy. In addition, it is worth considering the introduction of additional educational programs in the course of educating future surgeons to broaden the knowledge of anatomical variations and their importance.
Keywords: surgical complications anatomy; surgical errors; anatomical variations; arc of Buhler